An introduction to catchment runoff models with specific reference to ACRU, WASHMO and NPS - de Villiers, Gawie; Schmitz, Peter (Acta Academica: Critical views on society, culture and politics, 2024)
Catchment runoff models have been developed for widely differing purposes and are able to accommodate very different degrees of availability of hydrological data. The models are classified in three categories, namely as stochastic, empirical or deterministic models. This general orientation is followed by a more detailed discussion of three models; the model of the Agricultural Catchment Research Unit (ACRU), the Watershed Storm Hydrograph Multiple Options model (WASHMO) and the Non-Point Source model (NPS).